A double-headed hydra: Marine Le Pen's charisma, between political masculinity and political femininity. Issue 1 (2nd January 2020) - Geva, Dorit
ABSTRACT: Although charisma is more commonly associated with masculine leadership, Marine Le Pen (MLP) is a woman politician whom supporters view as charismatic. Combining theories of hegemonic masculinity, and hegemonic femininity, with Max Weber's typology of legitimate domination, this paper elaborates a framework for identifying how political masculinity and femininity are relationally structured within types of legitimate domination, including charismatic domination. I apply this framework to empirical analysis of the French radical rightwing leader and her supporters. Charisma, I suggest, is a form of political masculinity a woman can enact, but which allows for expression of political femininity. Drawing from participant observation data gathered on the French National Front between 2013 and 2017, and from interviews with party members, I show how activists viewed MLP as an admirably virile figure. Simultaneously, she was venerated for her feminine corporality, and her expression of feminine care, or caritas. Like a double-headed hydra, MLP was viewed as extraordinary due to her combined political masculinity and political femininity. Contra theories of hegemonic masculinity, MLP shows that a charismatic woman can perform hegemonic masculinity without being punished by supporters for doing so. Rational-bureaucratic domination, by contrast, is predominantly masculine, and allows for little expression of political femininity.